Enhanced Vernier Effect in Cascaded Fiber Loop Interferometers for Improving Temperature Sensitivity - Jianming Zhou; Yanyan Zhi; Junyi Zhang; Jianping Yao; Junkai Zhang; Jiejun Zhang (Sensors)
This work presents a high-sensitivity temperature sensing system utilizing an enhanced Vernier effect implemented in cascaded fiber loop interferometers. High-sensitivity temperature sensors based on the Vernier effect have broad application prospects, but the sensitivity of traditional measurement schemes is difficult to improve further due to the limited variation in the difference between two free spectrum ranges (FSRs). Our sensing system incorporates two fiber loop interferometers and a single-mode fiber to form a Vernier spectral response, characterized by two complementary optical filter responses. As the temperature of the sensing fiber changes, one FSR decreases, and the other increases, respectively, enhancing the difference value between the two FSRs to form an enhanced Vernier effect. Experimental results demonstrate that the temperature sensitivity of a traditional Vernier effect measurement is only −298.29 kHz/°C, while our proposed enhanced Vernier effect sensing system achieves a sensitivity of 618.14 kHz/°C, which is 92 times higher than that of a two-arm optical carrier-based microwave interferometry (OCMI) sensing system and 2.07 times higher than that of a traditional Vernier effect sensing system. This approach with an enhanced Vernier effect scheme based on cascaded fiber loop interferometers can be used to design high-sensitivity sensing systems for biometrics, smart cities, and the Internet of Things.